Randomized controlled trial of a water-soluble nail lacquer based on hydroxypropyl-chitosan (HPCH), in the management of nail psoriasis - Cantoresi F; Caserini M; Bidoli A; Maggio F; Marino R; Carnevale C; Sorgi P; Palmieri R (Dove Medical Press, 2014)
Franca Cantoresi,1 Maurizio Caserini,2 Antonella Bidoli,1 Francesca Maggio,1 Raffaella Marino,1 Claudia Carnevale,1 Paola Sorgi,1 Renata Palmieri21Department of Dermatology, Sapienza University, Rome, Italy; 2Scientific Department, Polichem SA, Lugano, Switzerland Background: Nail psoriasis occurs in up to 50% of patients affected by psoriasis, with a significant impact on quality of life that leads to a real clinical need for new therapeutic options. Aim: To confirm whether the strengthening and hardening properties of the hydroxypropyl-chitosan (HPCH) nail lacquer could improve the structure of the nail plates on psoriatic nails. Materials and methods: A randomized, double-blind, placebo controlled, parallel-group trial was carried out to evaluate the efficacy and tolerability of a hydrosoluble nail lacquer containing HPCH, Equisetum arvense, and methylsulfonylmethane on nail psoriasis. The test product or a placebo was applied once daily for 24 weeks to all fingernails. Efficacy assessments were performed on the target fingernail by means of the modified Nail Psoriasis Severity Index score. A cut-off score of 4 was considered to define the clinical cure rate (ie, Cure ≤4, Failure >4). Results: After 24 weeks, the clinical cure rate showed the statistically significant superiority of the HPCH nail lacquer compared to placebo in both the intention-to-treat (Fisher's exact test, P=0.0445) and the per protocol population (Fisher's exact test, P=0.0437). This superiority was already present after 16 weeks of treatment. Moreover, the analysis of the modified Nail Psoriasis Severity Index-50 showed a statistically significant clinical improvement after 12 weeks of treatment in comparison to the results obtained after 8 weeks (Fisher's exact test, P<0.05). Conclusion: The trial showed that HPCH nail lacquer could be a new, valid, effective, and safe option for decreasing the signs of nail dystrophy in psoriatic patients. Keywords: nail psoriasis, psoriatic onychodystrophy